CONSIDERATION OF ADDITIONAL ENERGY CONSUMPTION IN SMALL-SIZED REFRIGERATED SALES CABINET - Botov M.I.; Malakhov I.V.; Kobylyanskiy I.G. (Техника и технология пищевых производств)
One of the factors restraining production and storage of frozen and half-finished products is the high cost caused by additional operations of freezing and regeneration. Additional energy costs are determined by storage conditions. These energy costs are difficult to determine as there are no special studies on identification of additional leaks in the refrigeration apparatus when opening the doors. The energy losses are particularly significant for small-size refrigeration equipment used in food service industry and trade. At significant ratio of the door area to the volume of operating chamber specific for cooling and display cabinets the losses at door openings can amount up to 30%. Such mode of operation causes repeated-varying mode of heating-cooling of the stored products. The pulsation of temperature fields in the operating chamber caused by door openings can adversely affect the quality of stored half-finished products. The necessity of precise observation of foods storage conditions has been considered; the need of temperature pulsation recording in the apparatus operating volume when opening the doors has been shown. The experimental data characterizing the frequency of door openings are presented in the article. The experimental studies and the results of the solution of heat conductivity problem describing the temperature field in the frozen product volume under storage conditions in commercial refrigeration equipment - refrigerated sales cabinets are presented. The obtained analytical solution makes it possible to determine the rate of cooling (heating), specific energy consumption to maintain the required condition as well as to choose the optimum ratio of operating period duration and refrigerator shutdowns. A technical solution enabling to compensate the loss of cold when opening the doors is proposed.